2015
DOI: 10.1002/adhm.201500345
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Polycaprolactone 3D Nanofibrous Scaffold with Interconnected and Hierarchically Structured Pores for Bone Tissue Engineering

Abstract: For the first time, electrospun polycaprolactone (PCL) 3D nanofibrous scaffold has been developed by an innovative and convenient approach (i.e., thermally induced nanofiber self-agglomeration followed by freeze drying), and the scaffold possesses interconnected and hierarchically structured pores including macropores with sizes up to ≈300 μm. The novel PCL 3D scaffold is soft and elastic with very high porosity of ≈96.4%, thus it is morphologically/structurally similar to natural extracellular matrix and well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
199
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 253 publications
(207 citation statements)
references
References 45 publications
3
199
1
4
Order By: Relevance
“…Moreover, the high tunability and low cost enable gelatin to be a versatile polymer for biomedical applications. It has been recognized that nanofibrous scaffolds with connected macropore structure that mimic the natural ECM are favorable for osteoblastic differentiation and bone formation [5052]. Although our data confirmed that the GF scaffolds can non-specifically absorb a small amount of rhBMP2, the affinity of BMPs to gelatin scaffolds is still limited due to the absence of the BMP-binding moieties.…”
Section: Discussionmentioning
confidence: 43%
“…Moreover, the high tunability and low cost enable gelatin to be a versatile polymer for biomedical applications. It has been recognized that nanofibrous scaffolds with connected macropore structure that mimic the natural ECM are favorable for osteoblastic differentiation and bone formation [5052]. Although our data confirmed that the GF scaffolds can non-specifically absorb a small amount of rhBMP2, the affinity of BMPs to gelatin scaffolds is still limited due to the absence of the BMP-binding moieties.…”
Section: Discussionmentioning
confidence: 43%
“…In our recently published paper [22], a new strategy of thermally induced (nanofiber) self-agglomeration (TISA) followed by freeze drying has been reported; in specific, as-electrospun polycaprolactone (PCL) nanofibrous mats can first be converted into short individual nanofibers and tiny nanofibrous pieces, which can subsequently be utilized as building materials for making 3D electrospun PCL nanofibrous scaffolds. The resulting 3D scaffolds have the porosity of ~96% and possess the interconnected and hierarchically structured pores including macropores with sizes up to 300 µm.…”
Section: Introductionmentioning
confidence: 99%
“…Our in vitro cell differentiation results indicated that 3D electrospun PCL nanofibrous scaffolds (prepared via the TISA technique) were more favorable for chondrogenic (rather than osteogenic) differentiation, probably attributed to the relatively low stiffness/modulus of PCL [22]. Although these scaffolds could support bone morphogenetic protein 2 (BMP2) induced ectopic endochondral bone formation, new bones were identified merely in the surrounding areas but not inside the implanted scaffolds, suggesting that these scaffolds might need improvements to encourage/facilitate the bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospun PCL 3D nanofibrous with soft and highly porous scaffolds was developed in a study. In vivo studies indicated that this scaffold acts as an extracellular matrix for the regeneration of bone via a physiological endochondral ossification process (25).…”
Section: Poly(α-hydroxy Acids)mentioning
confidence: 99%